RNase III‐dependent down‐regulation of ftsH by an artificial internal sense RNA in Anabaena sp. PCC 7120. Issue 2 (13th May 2013) - Gao, Yuan; Gong, Yangmin; Xu, Xudong
Abstract RNase III is a group of dsRNA‐specific ribonucleases that play important roles in RNA processing and metabolism. Alr0280 and All4107 in Anabaena sp. PCC7120 are highly similar to RNase III enzymes. In vitro, recombinant Alr0280 showed RNase III activity. In the same cyanobacterium, the expression of ftsH (FtsH protease) could be suppressed by overexpression of an artificial sense RNA (aaftsH) that was complementary to aftsH, an internal antisense RNA. The aaftsH interference was abolished by inactivation of alr0280, the RNase III‐encoding gene, and restored by complementation of the mutant. A cyanobacterial homolog to hen1, an RNA methyltransferase gene, may also be required for the aaftsH interference. This is the first report of RNase III‐dependent sense RNA interference in cyanobacteria, and the underlying mechanism remains to be elucidated.